PENGARUH MORDAN AIR TAPAI KETAN HITAM DAN AIR TAPAI SINGKONG TERHADAP HASIL PENCELUPAN PADA BAHAN SUTERA MENGGUNAKAN EKSTRAK KULIT BUAH MANGGIS (Garcinia Mangostana L) - Hasanah, Uswatun; Adriani, Adriani; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2017)
This study aims to describe the name of the color (hue), the bright dark color (Value) and the color flatness of the silk dye results using mangosteen peel skin extract (Garcinia Mangostana l) with mordan water tapai black sticky and cassava tapai water. This type of research is an experimental research. The data used are primary data sourced from 15 panelists, then the collected data is processed and analyzed using ANOVA and Percentage. Immersion of silk material with mangosteen peel extract (Garcinia Mangostana l) without mordan produces Antique white color with bright value and flatness of flat color. Mordan Air Tapai Ketan Hitam is Pale Golden with value is quite bright and flat color of paa category is quite flat and mordan water tapai cassava is Almond off with equal value of light and flatness of color in flat category. The result of analysis of dark data of bright color (value) shows Fcount> Ftable = 3.320> 3. 22 It means there is significant influence to the dark of color (value) due to mordan influence. In the flatness of the color indicates Fcount> Ftable = 26.169> 3.885 This means that there is a significant effect on the color of the mordan effect.